2014
DOI: 10.1016/j.juro.2013.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Status and Progression or Regression of Lower Urinary Tract Symptoms in a General Adult Population Sample

Abstract: Purpose: To report progression and regression of lower urinary tract symptoms (LUTS) in a population-based cohort by race/ethnicity, sex, age and LUTS medication use. Materials and Methods: The Boston Area Community Health Survey enrolled 5,502 participants aged 30-79 years of black, Hispanic, or white race/ethnicity. Five-year follow-up interviews were completed by 4,144 (1,610 men, 2,534 women; conditional response rate of 80%). Population-weighted estimates of LUTS severity were assessed using American Ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 29 publications
1
18
0
1
Order By: Relevance
“…27 It is worth noting that studies based on symptoms reported by women of different race may be biased by culture-based differences in perceptions of symptoms. 29 …”
Section: Phase I: Predisposing Factors For Pelvic Floor Disordersmentioning
confidence: 99%
“…27 It is worth noting that studies based on symptoms reported by women of different race may be biased by culture-based differences in perceptions of symptoms. 29 …”
Section: Phase I: Predisposing Factors For Pelvic Floor Disordersmentioning
confidence: 99%
“…Three prospective studies found that higher body mass index (BMI) was associated with increased incidence of LUTS 57 , and one also found that a higher waist to hip ratio was similarly associated with an increased risk of LUTS 5 . Another prospective study recently reported that higher BMI was associated with an increase of ≥3 points in LUTS symptom score 8 . Two other prospective studies found no association between BMI and risk of LUTS, but did not adjust for any possible confounding factors, including age 9, 10 .…”
Section: Introductionmentioning
confidence: 99%
“…8 Parity and medical conditions, such as diabetes, obesity, and depression, are associated with prevalence and incidence of bladder symptoms. [9][10][11][12][13][14] Racial and gender differences in bladder symptoms, specifically symptoms of overactive bladder, such as incontinence or urgency, have also been reported. 4,11,15 The menopause transition is also associated with increased urinary complaints linked to the drastic reduction in endogenous estrogens, yet the literature remains unclear as to whether it is aging or reproductive stage that has the greater influence on bladder symptoms.…”
Section: Introductionmentioning
confidence: 99%